The Effects of Nitrogen Fertilizer Dosages on Anatomical Characters of Ipomoea batatas L. Leaf - Juwarno Juwarno; Sumarsono Sumarsono; Siti Samiyarsih (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2009)
The research was conducted in order to understand the effects of various nitrogen dosages on the anatomical characters of Ipomoea batatas leaf, and to find out the most influential dosage on the number and size of leaf anatomical characters. The characters observed consisted of thickness of cuticle, leaf, and palisade, as well as stoma size, and their density within mm2 of leaf surface. The method applied was experiments arranged in Completely Randomized Design. The results showed that all levels of nitrogen dosage affected the anatomical characters of sweet potato leaf while the most influential dosage was 200 kg urea per ha.